Clinical Outcomes of Titanium Zirconium and Titanium Dental Implants under Immediate Functional Loading in Posterior Mandibular Region - Aditi Verma; Kaushal Kishor Agrawal; Pooran Chand; Ramashanker; Shuchi Tripathi; Deeksha Arya (Wolters Kluwer Medknow Publications, 2024)
Background: Studies comparing the clinical performance of titanium zirconium (Ti-Zr) and titanium (Ti) dental implants subjected to immediate loading in the posterior mandibular region where occlusal forces are higher are sparse in the current literature. Hence, the study aimed to evaluate and compare the clinical outcomes of Ti-Zr and Ti dental implants under immediate functional loading in the mandibular posterior region. Methods: Forty participants fulfilling the predetermined selection criteria were randomly grouped based on dental implant used; Titanium zirconium (Ti-Zr):20, and Titanium (Ti):20. Dental implants were placed through a standard full-thickness mucoperiosteal flap approach and loaded immediately fulfilling the principle of implant protective occlusion. Clinical parameters including crestal bone loss (CBL), modified plaque index (MPI), probing depth (PD) and modified sulcular bleeding index (MSBI) were measured at baseline and follow-up visits (4, 8, and 12 months). Obtained data were compared with standard tests such as the t-test, Chi-square test, and Mann-Whitney U test. Results: On intergroup comparison, CBL was more in the Ti-Zr group as compared to the Ti group at 4 months (0.72 ± 0.16 mm versus 0.70 ± 0.13 mm), but it was less at 8 months (1.08 ± 0.16 mm versus 1.13 ± 0.13 mm) and 12 months (1.19 ± 0.17 mm versus 1.24 ± 0.12 mm) but the difference was not statistically significant (P > 0.05). Mann-Whitney test also revealed no statistically significant difference in MPI, PD and MSBI at 4 months, 8 months and 12 months recall (P > 0.05). Conclusions: CBL and periodontal parameters of Ti-Zr dental implants were found similar to Ti dental implants under immediate loading in the posterior mandibular region. However, further studies are needed to determine its long-term efficacy and cost-effectiveness.